تحرير الكلام في قول الإمام ابن القيم أن غير ربا النسيئة تحريمه من باب سد الذريعة (Revue El-Wahat pour les Recherches et les Etudes, 2020)
Bn Alkayim Said: "Riba Has Two Aspects: Overt And Covert. The Overt Riba Was Prohibited Owing To The Tremendous Harm It Causes; The Covert Riba Was Also Prohibited Because It Leads To The Overt  One. The Prohibition Of The First Is Related To The Objectives (Of Shariah); And The Prohibition Of The Second Is Related To The Means (Leading To Haram)." Since Muslim Scholars Agree That Overt Riba, Known As Riba Of Loans, Is The One Prohibited In Quran, For The Reason Of Prohibition Of Which Is Completely Anid Explicitly Expressed In The Words Of The Text Of Quran, As Stated In The Present Study, Unlike The Other Types Of Riba Where The Reason Is Of Prohibition Is Expressed In Different Words. Thus, This Study Agrees With Ibn Alkayim Affirming That Riba Al-Fadl (Riba Of Surplus) Is Not Prohibited For Itself, It Is Prohibited To Block The Way That Leads To Riba. Key Words - ( Riba, Bn Alkayim, The Usury Bug, The Overt Riba, Bridging The Pretext).